If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(S + 4) = -12 Reorder the terms: -8(4 + S) = -12 (4 * -8 + S * -8) = -12 (-32 + -8S) = -12 Solving -32 + -8S = -12 Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -8S = -12 + 32 Combine like terms: -32 + 32 = 0 0 + -8S = -12 + 32 -8S = -12 + 32 Combine like terms: -12 + 32 = 20 -8S = 20 Divide each side by '-8'. S = -2.5 Simplifying S = -2.5
| 13s-3=10 | | x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 | | 18.75+x=26.55 | | 4x-8=5x+5+75 | | 6x-2x+60= | | 2(3d-4)=2(2d+6) | | y=-3+2+5 | | (3v+5)(8+v)=0 | | 3r-18=3 | | K^2+7x=0 |